Study of Law Number 1 of 2023 concerning the Criminal Code (KUHP) - Rahmadianto, Muhammad (Enigma in Law, 2023)
The Criminal Code (KUHP) Law Number 1 of 2023 is a modification of the existing Criminal Code that has been in force since 1918. The reform of the Criminal Code aimed to align with advancements in criminal law in Indonesia and address the evolving legal requirements of society. The amendment to the Criminal Code encompasses several modifications, including the incorporation of novel criminal offenses, such as offenses against the environment, offenses against public assets, and offenses against human rights. Abolition of antiquated penal offenses, such as adultery, abortion, and offenses against moral principles. Revisions to the definition of criminal offenses, such as modifications to the definition of theft, embezzlement, and domestic violence, The amendment to the Criminal Code has both favorable and unfavorable consequences. Overall, many consider the amendment of the Criminal Code a favorable measure that aligns with advancements in criminal law in Indonesia and addresses the increasing legal requirements of society. This change is also deemed capable of offering enhanced legal safeguards for the community while simultaneously achieving justice and legal clarity.